Crocker Range National Park, Sabah, as a refuge for Borneo’s montane herpetofauna - Das, I. (Provo, Utah :Amphibian & Reptile Conservation, 2006)
Crocker Range National Park in Sabah (East Malaysia), northern Borneo, is an exceptional area for herpetological diversity. Inventories of the Park are incomplete, but show high diversity, as well as regional endemicity shared with the adjacent and more well-known Gunung Kinabalu National Park. The montane ecosystem of the Range offers refuge for a number of rare herpetofaunal taxa, including Stoliczkia borneensis, Rhabdophis murudensis, Oligodon everetti, Philautus bunitus, Ansonia anotis, Sphenomorphus aesculeticola, and undescribed species of squamates of the genera Sphenomorphus and Gongylosoma. The 59 species of amphibians and 45 species of reptiles now recorded from the Range represent 39 and 16.2 per cent of the total Bornean amphibian and reptile fauna, respectively. The high levels of deforestation of the surrounding regions of Borneo, particularly lowland rainforests, highten the importance of protection of primary forests of northern Borneo’s Crocker Range.